From mythos to logos : Andrea Palladio, Freemasonry, and the triumph of Minerva - Coughlin, Michael Trevor (Brill's studies in intellectual history, 2019)
"In his new book From Mythos to Logos : Andrea Palladio, Freemasonry and the Triumph of Minerva, Michael Trevor Coughlin provides an interpretive lens to explore how myth was used to encode sixteenth-century Italian works of architecture and their frescoed interiors with logos--providing powerful insights that promote a way of being in a world in which peace and freedom are the greatest hallmarks of society. Leaning heavily on the intersection between myth and philosophy, Coughlin convincingly argues Freemasonry began in the Italian city of Vicenza in 1546, offering fresh insight into the origin of Freemasonry, one of the most powerful and longstanding organizations in the world--one in the midst of a popularity and membership boom that is unprecedented"--